2022
DOI: 10.3389/fmicb.2022.957809
|View full text |Cite
|
Sign up to set email alerts
|

Indigofera tinctoria L. leaf powder promotes initiation of indigo reduction by inducing of rapid transition of the microbial community

Abstract: Water-insoluble indigo is solubilized by the reducing action of microorganisms which occurs during fermentation. In natural indigo fermentation, composted leaves of Polygonum tinctorium L. (sukumo) are the raw material that has been used as both the indigo source and the bacterial inoculum. Ideally, indigo reduction occurs shortly after preparation of the fermentation vat. The time-to-reduction depends on the quality of the sukumo and the methods for preparation and management of the fermentation batch. We est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The period from the fermentation preparation to indigo reduction initiation differs depending on the procedure and quality of raw materials. Transitional changes in the redox state of indigo may be related to changes in the microbiota, which is in turn, associated with the indigo reduction initiation, as previously have suggested using clone library analysis (Aino et al, 2010) and nextgeneration sequencing (Tu et al, 2019a(Tu et al, ,b, 2021Lopes et al, 2021Lopes et al, , 2022Nakagawa et al, 2022). On days 0-1, oxygen metabolizable Bacillaceae (e.g., Sutcliffiella cohnii) and Actinobacteria (e.g., Nocardiopsis ganjiahuensis) appear, following which their numbers significantly decrease during days 2-10 as the redox potential (ORP) decreases due to their consumption of oxygen.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…The period from the fermentation preparation to indigo reduction initiation differs depending on the procedure and quality of raw materials. Transitional changes in the redox state of indigo may be related to changes in the microbiota, which is in turn, associated with the indigo reduction initiation, as previously have suggested using clone library analysis (Aino et al, 2010) and nextgeneration sequencing (Tu et al, 2019a(Tu et al, ,b, 2021Lopes et al, 2021Lopes et al, , 2022Nakagawa et al, 2022). On days 0-1, oxygen metabolizable Bacillaceae (e.g., Sutcliffiella cohnii) and Actinobacteria (e.g., Nocardiopsis ganjiahuensis) appear, following which their numbers significantly decrease during days 2-10 as the redox potential (ORP) decreases due to their consumption of oxygen.…”
Section: Introductionmentioning
confidence: 80%
“… Lopes et al (2021) also reported the importance of “PTS” in fermentation, which accelerated indigo reduction by the addition of Indian indigo leaf powder during early fermentation. The importance of “starch and sucrose metabolism” in indigo reduction has been reported in comparative studies between of rapid and slow time-to-indigo reduction sukumo ( Lopes et al, 2022 ). Using various preparation samples in this study, we clarified the significance of the two subpathways, “PTS” and “starch and sucrose metabolism,” by assessing the relationship between dyeing intensity and functional abundance during early fermentation.…”
Section: Discussionmentioning
confidence: 99%